Correction: Tracking insect outbreaks: a case study of community-assisted moth monitoring using sex pheromone traps - Rob C. Johns (Canadian Science Publishing, 2020)
Re: Carleton RD, Owens E, Blaquière H, Bourassa S, Bowden JJ, Candau J-N, DeMerchant I, Edwards S, Heustis A, James PMA, Kanoti AM, MacQuarrie CJK, Martel V, Moise ERD, Pureswaran DS, Shanks E, and Johns RC. 2020. Tracking insect outbreaks: a case study of community-assisted moth monitoring using sex pheromone traps. FACETS 5: 91-104. doi.org/10.1139/facets-2019-0029. In the originally published article, the photo credit is missing from Figure 1. The corrected figure is shown on the following page. The article has been corrected accordingly.